Agreements and Potential Fraud Arising in the Phenomenon of Online-Based Gambling Game - Hediati, Febri Noor (Universitas Islam Lamongan, 2025)
In general, the impact of technological development has many benefits for life. However, on the other hand, this technology can also be used for illegal activities such as online gambling. Online gambling that has developed by utilizing technology has reached all circles. This phenomenon brings significant negative impacts, such as addiction, financial loss, family destruction, and increased potential for criminal acts. The government has made efforts to eradicate online gambling such as blocking gambling content, although the effectiveness of these efforts still faces challenges due to the emergence of new gambling sites that continue to grow. This research uses doctrinal method with the approach of legislation, primary legal materials, and secondary legal materials. One of the conditions for the validity of an agreement in Article 1320 of the Civil Code is something that is halal. The object of the gambling agreement is something that is prohibited by law and religion, so it is not halal. In online gambling agreements, there is a lot of potential for fraud in it which violates 1338 (3) of the Civil Code, due to the absence of elements of bad faith. Online gambling involves agreements that are often unilateral and vulnerable to manipulation by the bookies such as failure to process deposits, refusal to disburse winnings, and unilateral account blocking. A collaborative approach between the government, religious leaders, educational institutions and parents is needed for prevention. Legal education and digital literacy are important steps in providing awareness of the dangers of online gambling. In addition, the government needs to optimize technology to detect and eradicate gambling transactions, as well as provide strict law enforcement against the perpetrators and promoters of online gambling. With strong synergy, it is hoped that online gambling can be comprehensively eradicated in order to protect the nation's next generation.